Automated car driver assisted : road lane detection and tracking using vision sensor - Nor Sakinah , Abdul Shukor (2012)
A Lane Departure Warning (LDW) system is one of the systems of the Automated Car Driver Assisted system. The lane departure warning system is designed to warn the driver when the vehicle starts to move out from the actual lane without any intention of the driver to change from the initial lane path. This system is designed to decrease the number of road accident those are frequently occurred because of the driver error, distraction and drowsiness. This LDW system can also be applied on many real world applications such as security control freeway, driving training, autonomous navigation and the visually impaired assistant. The LDW system is based on visual sensor that is usually mounted behind the windshield of the vehicle, laser sensor which is mounted on the front of the vehicle and infrared sensor which is mounted either behind the windshield or under the vehicle. While driving a vehicle, it is unknown whether the driver driving with normal behavior or not. Human error such as drowsiness and distraction while driving is the biggest factor of road accidents. A LDW system is a mechanism to warn the driver when the vehicle starting to depart of the lane on the road and help in decrease the number of accidents cause by the problems above.